NEW EDUCATIONAL INNOVATIVE ASPECTS OF DECENTRALIZATION OF MANAGEMENT IN EDUCATIONAL INSTITUTIONS (World Science, 2018)
This paper argues that today, while building democratic, social state, the implementation of the reform of the administrative-territorial system and the system of local self-government (decentralization) is one of the key tasks of the Ukrainian authorities. Considering that education is one of the largest sectors of public services used by the population, ranging from the level of the individual community, its reformation becomes a priority among other reforms in Ukraine.